Novel treatment options for anaplastic thyroid cancer. Issue 4 (4th July 2017) - Fallahi, Poupak; Ruffilli, Ilaria; Elia, Giusy; Ragusa, Francesca; Ulisse, Salvatore; Baldini, Enke; Miccoli, Mario; Materazzi, Gabriele; Antonelli, Alessandro; Ferrari, Silvia Martina
ABSTRACT: Introduction : Several genetic alterations have been identified in different molecular pathways ofanaplastic thyroid cancer (ATC) and associated with tumor aggressiveness and progression (BRAF, p53, RAS, EGFR, VEGFR-1, VEGFR-2, etc). New drugs targeting these molecular pathways have beenrecently evaluated in ATC. Areas covered : We review the new targeted therapies of ATC. Interesting results have been reported with molecules targeting different pathways, as: a-BRAF (dabrafenib/trametinib, vemurafenib); b-angiogenesis (sorafenib, combretastatin, vandetanib, sunitinib, lenvatinib, CLM3, etc); c-EGFR (gefitinib); d- PPARγ agonists (rosiglitazone, pioglitazone, efatutazone). In patients with ATC treated with lenvatinib, a median overall survival of 10.6 (3.8–19.8) months was reported. In order to bypass the resistance to the single drug, the capability of targeted drugs to synergize with radiation, or chemotherapy, or other targeted drugs is explored. Expert commentary : New, affordable and individual genomic analysis combined with the opportunity to test these new treatments in primary cell cultures from every ATC patient in vitro, may permit the personalization of therapy. Increasing the therapeutic effectiveness and avoiding the use of ineffective drugs. The identification of new treatments is necessary, to extend life duration guaranteing a good quality of life. To bypass the resistance to asingle drug, the capability of targeted drugs to synergize with radiation, or chemotherapy, or othertargeted drugs is explored. Moreover, new affordable individual genomic analysis and the opportunity totest these novel treatments in primary cell cultures from every ATC patient in vitro, might permit topersonalize the therapy, increasing the therapeutic effectiveness and avoiding the use of ineffectivedrugs.